Political reforms asserting civic sovereignty - Panadiker, V A Pai (Ed.); Kashyap, Subhash (Ed.) (Delhi Konark, 2001)
Political reforms attempts to identify the problems analyse political economic and systematic causes examine policy; option and suggests a concrete blueprint for political sovereignty of the citizens. It covers matters such as structural reforms of the el
Under auspices of centre for policy Research, New Delhi
Keywords: India-Politics and government; Sovereignty; Political science